DEVELOPING ISLAMIC FINANCIAL TECHNOLOGY IN INDONESIA - Aam Slamet Rusydiana (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2018)
Financial technology in Indonesia is an untapped market opportunity. As the world’s largest population Muslim country, the prospects for Islamic fintech in Indonesia seem very bright. This study tries to answer what problems, foundations and key ecosystem or stakeholders are involved in the development of Islamic fintech in Indonesia using Interpretive Structural Model (ISM) approach. The core problems faced in the development of Islamic financial technology industry are: Lack of policy instruments guarding the fintech work process, and availability of human resources for fintech. The core strategies or foundations that’s needed in framework of Islamic fintech development are: Ability to manage and analyze data in big data era, and Human resources in digital marketing. For the aspects of Ecosystem or Actors involved in the development of Islamic fintech in Indonesia, the important actor is: Government or regulator, Educational institutions (universities), and also Existing industries (banks and other financial institutions).